`KOMPOSISI RAYAP DI KEBUN GAMBIR DI KANAGARIAN SIGUNTUR MUDA KECAMATAN KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Aidi, Rido; Nurhadi, Nurhadi; Safitri, Elza (STKIP PGRI Sumbar, 2013)
AbstractGrowth of human being activity to fulfill requirement of its life oftentimes change role of termite. Environmental which do not annoyed termite have role in process of decomposition of organic garbage. Change of forest areal become agriculture areal, plantation oftentimes change role of termite become pest. In Kanagarian Siguntur in general society represent farmer of gambir, so that most forest processed to become garden of gambir, which can disturb habitat of termite ( Isoptera). Hence have been done research of concerning Composition Termite at Garden of Gambir in Kanagarian Siguntur Muda, District Of Koto XI Tarusan Sub-Province Pesisir Selatan. This Research is done to know termite composition ( Isoptera) in garden of gambir. This research is done in Agustus-September 2013, with used method of hand sort with two station. Station I is garden of gambir and station II is forest around garden of gambir. Intake sample of termite is done broadly used plot 50 X 50 cm, that consist of 3 substasiun. Apart between substasiun 20 m. Each substasiun consist of 5 plot which is the each aparting 10 m. Pursuant to result of research which have been done by composition termite in garden of gambir found as many as two family which consist of three subfamili, three species, and 639 individual. Meanwhile at forest, found composition termite as many as the two family which consist of four subfamili, four species, and 875 individual. chemical Physics factor of temperature ground, ground water rate, ground pH, and rate of C organic of ground according to support life of termite.